2020
DOI: 10.1538/expanim.19-0076
|View full text |Cite
|
Sign up to set email alerts
|

Role of MafB in macrophages

Abstract: The transcription factor MafB regulates macrophage differentiation. However, studies on the phenotype of Mafb-deficient macrophages are still limited. Recently, it was shown that the specific expression of MafB permits macrophages to be distinguished from dendritic cells. In addition, MafB has been reported to be involved in various diseases related to macrophages. Studies using macrophage-specific Mafb-deficient mice show that MafB is linked to atherosclerosis, autoimmunity, obesity, and ischemic stroke, all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 85 publications
(105 reference statements)
0
43
0
Order By: Relevance
“…In addition, it was observed that MAFB limits the ability of M-CSF to differentiate hematopoietic stem cells towards the myeloid program (70). MAFB can also impact the function of macrophages in several pathological models (73)(74)(75)(76). In the context of metabolic disease, animals harboring MAFB-deficient macrophages were shown to be more susceptible to obesity in a hyper caloric setting 75 Macrophages adapt to the tissue environment in which they reside, and are, therefore, different in every tissue (4,43,77).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was observed that MAFB limits the ability of M-CSF to differentiate hematopoietic stem cells towards the myeloid program (70). MAFB can also impact the function of macrophages in several pathological models (73)(74)(75)(76). In the context of metabolic disease, animals harboring MAFB-deficient macrophages were shown to be more susceptible to obesity in a hyper caloric setting 75 Macrophages adapt to the tissue environment in which they reside, and are, therefore, different in every tissue (4,43,77).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, AMs clearly proliferate in response to colony-stimulating factors GM-CSF and M-CSF ( Chen et al, 1988 ; Draijer et al, 2019 ), with mTORC1 ( Deng et al, 2017 ) and the transcription factors Bhlhe40 and Bhlhe41 ( Rauschmeier et al, 2019 ) being responsible for this process. MafB, another transcription factor that is necessary for maintenance of AM numbers ( Sato-Nishiwaki et al, 2013 ), is also expressed at very low levels in AMs ( Hamada et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Splenic macrophages play significant roles in blood filtration (Klei, Meinderts, Berg, & Bruggen, 2017). MafB is a basic leucine zipper transcription factor encoded by the Mafb gene and was found to be required for several processes including macrophage differentiation and islet beta cells development (Abdellatif et al, 2015; Abdellatif et al, 2016; Hamada, Tsunakawa, Jeon, Yadav, & Takahashi, 2020). MafB was also reported to be expressed by large proportion of splenic macrophages in mice (Lloyd, Phillips, Cooper, & Dunbar, 2008).…”
Section: Discussionmentioning
confidence: 99%